2010
DOI: 10.5229/jkes.2010.13.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Defective-Structure Li4Mn5O12by Combustion Method and Its Application to Hybrid Capacitor

Abstract: 초 록o C for 5 h had larger first discharge capacity (41.5 mAh/g) at 1C-rate for 3.7~4.4 V than other calcined samples. Moreover, applying to hybrid capacitor, it had good discharge capacity (24.74 mAh/g or 10.46 mAh/cc) at 100 mA/g for 1~2.5 V and higher energy density (39 Wh/kg or 16.49 Wh/cc) at same condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The waxberry-like nanosphere Li4Mn5O12 consists of many small Li4Mn5O12 balls that have unsmooth surfaces and multiple pores-the result corresponds to the SEM image above. It is worth noting that the morphologies of waxberry-like nanosphere and raspberry-like nanosphere Li4Mn5O12 had not been attained by the simple methods reported before [1,16,[21][22][23][24][25]. The distribution of elements in the material is characterized by mapping, which was shown in Figure S1.…”
Section: Characterization and Measurementmentioning
confidence: 98%
“…The waxberry-like nanosphere Li4Mn5O12 consists of many small Li4Mn5O12 balls that have unsmooth surfaces and multiple pores-the result corresponds to the SEM image above. It is worth noting that the morphologies of waxberry-like nanosphere and raspberry-like nanosphere Li4Mn5O12 had not been attained by the simple methods reported before [1,16,[21][22][23][24][25]. The distribution of elements in the material is characterized by mapping, which was shown in Figure S1.…”
Section: Characterization and Measurementmentioning
confidence: 98%
“…However, the perovskite oxides synthesized via solid-state reactions and sol-gel methods exhibit low specific surface areas due to a high calcination temperature of 1073-1173 K, inducing particle agglomeration [29][30][31]. In recent years, several research groups have reported that transition metal oxides containing small particle sizes and high specific areas can be fabricated via low-temperature heat treatment, resulting in excellent electrochemical properties and structural stability [32][33][34]. Crystalline particles with high purity and uniform crystal size can be obtained via hydrothermal synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] 1) Therefore, we expect that it is possible to synthesize at low temperature for short time as well as Li 2 Mn 3 O 7 is also possible to use cathode material in hybrid capacitor. Hence, hybrid capacitor using Li 2 Mn 3 O 7 has been studied, yet.…”
Section: Introductionmentioning
confidence: 99%